Integration with complex numbers a primer on complex analysis - McCluskey, Aisling; McMaster, Brian (Oxford University Press, 2022)
This volume offers a reader-friendly contemporary balance between idea, proof, and practice, informed by several decades of classroom experience and a seasoned understanding of the backgrounds, motivation and competing time pressures of today's student cohorts.